Temporal and Spatial Dynamics of Surface Water Temperature Changes in China's Major Lakes - Haimei Duan; Kun Yang; Xiaolu Zhou; Yi Luo (Water Resources Research, 2025)
Abstract Globally the lake surface water temperature (LSWT) has shown an upward trend and exhibits significant spatial heterogeneity,but revious studies have indeed delved it under current period. Here, we utilized the characteristics of LSWT variation in major lakes of China over two centuries. First we used the AIR2WATER model to constructed the data set of LSWT in Chin Chinese major lakes based on the data from CMIP6. Considering the rapid urbanization and climate change, the year of 1900–2014 can be divided into two phases: A stable period (1900–1970‐Phase I, 0.01°C/10a) and a warming period (1971–2014‐ Phase II, 0.16°C/10a). For the future (2015–2100), under the low emission scenario model (SSP1‐RCP2.6, 0.12°C/10a); under the medium emission scenario model (SSP2‐RCP4.5, 0.18°C/10a); and under the high emission scenario model (SSP5‐RCP8.5, 0.38°C/10a). We have designed three spatial classes to analyze the characteristics of LSWT of China major lake. Particularly, when analyzing the spatial pattern based on China's famous population‐economic demarcation line (the Hu Huanyong Line), we found that the LSWT growth rate in lakes east of the Hu Huanyong Line is higher than that in lakes to the west in Phase II, as well as under the SSP1‐RCP2.6 and SSP2‐RCP4.5 scenario models. However, in Phase I and under the SSP5‐RCP8.5 scenarios, the LSWT growth rate in lakes east of the Hu Huanyong Line is lower than that in the west. This study helps improve our understanding of China's major lakes and their changing mechanisms under the warming climate.